PERANGKAT LUNAK PERENCANAAN PERLUASAN KAPASITAS JARINGAN TELEKOMUNIKASI - Budi Santoso (NIM : 23597036), Purwadi
Abstract : In this tesis I have developed a software for decision support system for capacity planning. This software will propose when a telecommunication need to capacity planning and how much capacity should to be added. This software required a collection of data like capacity cost function, discount rate or price inflation, time horison with interval and growth value or costumer condition (if growth is unknown). Software will give a value when capacity expansion shoud be added in year and how much capacity should be added to that telecommunication in unit. Linear cost function and exponential cost function is available as capacity cost function. Financial cost criteria is used for computing so present worth analysis should be applied for analysis. I apply this analysis to develop this application with forward dynamic programming method to solve that problem. Array structure is used when application running and file of real to save a collection of data.